Efficacy of platelet-rich plasma as a shielding technique after endoscopic mucosal resection in rat and porcine models - Lorenzo-Zúñiga, Vicente; Boix, Jaume; Moreno de Vega, Vicente; Bon, Ignacio; Marín, Ingrid; Bartolí, Ramón (Endoscopy International Open, 2016)
Background and study aims: The aims were to assess the efficacy of endoscopic application of Platelet-rich plasma (PRP) to prevent delayed perforation and to induce mucosal healing after endoscopic resections.Patients and methods: Colonic induced lesions were performed in rats (n = 16) and pigs (n = 4). Animals were randomized to receive onto the lesions saline (control) or PRP. Animals underwent endoscopic follow-up. Thermal injury was assessed with a 1 – 4 scale: (1) mucosal necrosis; (2) submucosal necrosis; (3) muscularis propria necrosis; and (4) serosal necrosisResults: Saline treatment showed 50 % of mortality in rats (P = 0.02). Mean ulcerated area after 48 hours and 7 days was significantly smaller with PRP than with saline (0.27 ± 0.02 cm2 and 0.08 ± 0.01 cm2 vs. 0.56 ± 0.1 cm2 and 0.40 ± 0.06 cm2; P < 0.001). The incidence of thermal injury was significantly lower with PRP (1.25 ± 0.46) than in controls (2.25 ± 0.50); P = 0.006. The porcine model showed a trend toward higher mucosal restoration in animals treated with PRP than with saline at weeks 1 and 2 (Median area in cm2: 0.55 and 0.40 vs. 1.32 and 0.79)Conclusions: Application of PRP to colonic mucosal lesions showed strong healing properties in rat and porcine models.